PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PEMUTUSAN HUBUNGAN KERJA (PHK) DENGAN ALASAN EFISIENSI AKIBAT PANDEMI COVID 19: PERLINDUNGAN HUKUM TERHADAP PEKERJA DALAM PEMUTUSAN HUBUNGAN KERJA (PHK) DENGAN ALASAN EFISIENSI AKIBAT PANDEMI COVID 19 - Agung Prasetyo Wibowo Agung (Fakultas Hukum Universitas Kristen Indonesia, 2021)
Due to restrictions placed in order to prevent the spread of Covid-19, including the closure of company operations, the potential for companies to be forced out of business is relatively large. There have been many layoffs for employees. Termination of employment is closely related to the reason for efficiency caused by the impact of Covid-19. The problem in this writing is how companies carry out Termination of Employment (PHK) on the grounds of legitimate efficiency according to the Manpower Law and How Legal Protection for Workers in Termination of Employment for Efficiency Reasons as a Result of the Covid-19 Pandemic. Based on the Manpower Act. This type of research is normatid legal research which is focused on positive legal norms in the form of statutory regulations, to find the truth based on the logic of legal science from the normative side. The results showed that with the Covid pandemic, every company was forced to be able to continue its business. This condition requires every company to be able to optimize production factors in order to operate. To realize this condition, every worker as a factor of production is required to be productive in carrying out their work with the work standards set by the company. If workers are proven to be unproductive at work, the employer will take action in the form of termination of employment (PHK) as an efficiency measure. The law does not prohibit entrepreneurs from taking such efficiency measures, but efficiency measures will be invalid if the reasons, procedures and conditions specified are not fulfilled in accordance with the applicable regulations. Keywords: Termination of Employment, efficiency reasons, Legal Protection, Covid-19 Pandemic